Polski wywiad cywilny w Jugosławii w latach 1969–1990. Personalia i działalność - Zaćmiński, Andrzej (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2025)
This article examines the history of the Polish civil intelligence station (the so-called ‘residency’) in Yugoslavia, and later the operational centre of Department I of the Ministry of Internal Affairs, codenamed ‘Mrowie’. The author sought to address several research questions: What factors influenced its activities? What was the structure of its staff ? And what competencies did its officers possess? Additionally, the article outlines the intelligence tasks and operational methods employed by the station.
p. 155-181
Summary in English and Russian.
Keywords: civil intelligence of the Polish People’s Republic; Ministry of Internal Affairs; foreign policy of the Polish People’s Republic; People’s Poland; Yugoslavia; intelligence service - Poland - history; Poland. Ministerstwo Spraw Wewnętrznych i Administracji - history; Yugoslavia - relations - Poland - 1945-1990; Poland - relations - Yugoslavia - 1945-1990